Karl Rahner on Patristic Theology and Spirituality - Peterson, Brandon R. (Philosophy & theology, 2015)
A great amount of scholarly attention has been devoted to Karl Rahner’s early philosophical writings, but his theological work from the same time period remains only marginally known. While his dissertation in philosophy, Spirit in the World, has been published in multiple editions and in many languages, his dissertation in theology, E latere Christi, was only available in archives until it was published in the third volume (1999) of his collected works, Sämtliche Werke. Exploring the content of this third volume which contains Rahner’s early writing on the spirituality and theology of the Church Fathers, this article illuminates a neglected part of Rahner’s career: his fascination with patristic thought during his early, formative years. It also identifies themes in these early writings which reappear in his more well known mature writings on the theology of das Symbol, soteriology, mystery, and the importance of historical theology for the activity of today’s theologian.